Comparison of Gonioscopy and Anterior Segment OCT for Detecting Angle Closure in Different Quadrants of Anterior Chamber Angle in Angle Closure Glaucoma: Doi: 10.36351/pjo.v39i2.1539 - Imran, Khadeeja; Khan, Nida Armoghan; Jahan Zaib, Hafiz Muhammad; Nazir, Fahmina; Khalid, Amina (Pakistan Journal of Ophthalmology, 2023)
Purpose: To measure angle of anterior chamber with Gonioscopy and compare with anterior segment OCT. Study Design: Descriptive observational study. Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Pakistan institute of Medical Sciences, Islamabad from 1st March 2021 to 31st August 2021. Methods: A total number of 102 patients participated in the study. Study included participants older than 30 years of age, of either gender, who were either diagnosed as a case of angle closure-Glaucoma or were angle closure-Glaucoma suspect. Sampling was done using convenient sampling technique. The selected patients underwent gonioscopy and the anterior segment OCT and the grades of the angle were determined. Grading was compared between the two techniques. The collected data was analyzed by using SPSS 23 version. Result: The mean age of patients was 59.16 ± 6.03 years. Out of 102 patients, 34 (33.3%) patients were male and 63 (66.7%) patients were female. The mean intraocular pressure was 17.80 ± 4.25 (mmHg). The accuracy of angle closure detection by Gonioscopy was 35.3% and by anterior segment, OCT was 60.8%. The p value was significant in both the groups. The Anterior segment OCT turned out to be better than Gonioscopy. Conclusion: Anterior segment OCT is more efficient in determination of angle of anterior chamber than gonioscopy. Using anterior segment OCT to examine anterior chamber angle and surrounding tissues helps in diagnosing early stages of disease and directing therapy.